Hands-on cybersecurity for finance identify vulnerabilities and secure your financial services from security breaches - Ozkaya, Erdal; Aslaner, Milad (Packt Publishing, 2019)
A comprehensive guide that will give you hands-on experience to study and overcome financial cyber threats Key Features Protect your financial environment with cybersecurity practices and methodologies Identify vulnerabilities such as data manipulation and fraudulent transactions Provide end-to-end protection within organizations Book Description Organizations have always been a target of cybercrime. Hands-On Cybersecurity for Finance teaches you how to successfully defend your system against common cyber threats, making sure your financial services are a step ahead in terms of security. The book begins by providing an overall description of cybersecurity, guiding you through some of the most important services and technologies currently at risk from cyber threats. Once you have familiarized yourself with the topic, you will explore specific technologies and threats based on case studies and real-life scenarios. As you progress through the chapters, you will discover vulnerabilities and bugs (including the human risk factor), gaining an expert-level view of the most recent threats. You'll then explore information on how you can achieve data and infrastructure protection. In the concluding chapters, you will cover recent and significant updates to procedures and configurations, accompanied by important details related to cybersecurity research and development in IT-based financial services. By the end of the book, you will have gained a basic understanding of the future of information security and will be able to protect financial services and their related infrastructures. What you will learn Understand the cyber threats faced by organizations Discover how to identify attackers Perform vulnerability assessment, software testing, and pentesting Defend your financial cyberspace using mitigation techniques and remediation plans Implement encryption and decryption Understand how Artificial Intelligence (AI) affects cybersecurity Who this book is for Hands-On Cybersecurity for Finance is for you if you are a security architect, cyber risk manager, or pentester looking to secure your organization. Basic understanding of cybersecurity tools and practices will help you get the most out of this book.